T-cell receptor signaling induces proximal Runx1 transactivation via a calcineurin–NFAT pathway - Wong, W.F.; Looi, C.Y.; Kon, S.; Movahed, E.; Funaki, T.; Chang, L.Y.; Satake, M.; Kohu, K. (John Wiley & Sons, 2014)
Runx1 transcription factor is a key player in the development and function of T cells. Runx1 transcripts consist of two closely related isoforms (proximal and distal Runx1) whose expressions are regulated by different promoters. Which Runx1 isoform is expressed appears to be tightly regulated. The regulatory mechanism for differential transcription is, however, not fully understood. In this study, we investigated the regulation of the proximal Runx1 promoter in T cells. We showed that proximal Runx1 was expressed at a low level in naïve T cells from C57BL/6 mice, but its expression was remarkably induced upon T-cell activation. In the promoter of proximal Runx1, a highly conserved region was identified which spans from −412 to the transcription start site and harbors a NFAT binding site. In a luciferase reporter assay, this region was found to be responsive to T-cell activation through Lck and calcineurin pathways. Mutagenesis studies and chromatin immunoprecipitation assay indicated that the NFAT site was essential for NFAT binding and transactivation of the proximal Runx1 promoter. Furthermore, TCR signaling-induced expression of proximal Runx1 was blocked by treatment of cells with cyclosporin A. Together, these results demonstrate that the calcineurin–NFAT pathway regulates proximal Runx1 transcription upon TCR stimulation.